Resistin as potential biomarker for chronic periodontitis: A systematic review and meta-analysis - Akram, Z.; Rahim, Z.H.A.; Taiyeb-Ali, T.B.; Shandan, M.S.A.; Baharuddin, N.A.; Vaithilingam, R.D.; Safii, S.H. (Elsevier, 2017)
Objectives: To determine the serum and gingival crevicular fluid (GCF) levels of resistin between individuals with chronic periodontitis (CP) and those without CP, and to evaluate the role of resistin in CP.